2021
DOI: 10.3390/ijms22158242
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Immunotoxicity: Stressors and Evaluators

Abstract: The immune system defends the body against certain tumor cells and against foreign agents such as fungi, parasites, bacteria, and viruses. One of its main roles is to distinguish endogenous components from non-self-components. An unproperly functioning immune system is prone to primary immune deficiencies caused by either primary immune deficiencies such as genetic defects or secondary immune deficiencies such as physical, chemical, and in some instances, psychological stressors. In the manuscript, we will pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 213 publications
(241 reference statements)
0
13
0
1
Order By: Relevance
“…Several studies stated that BPA can bind T cells affecting Th17, Th1, and Th2 differentiation [ 50 ]. BPA significantly increased the IFN-γ and IL-4 secretion in animal models, suggesting a possible upregulation of the Th1 response [ 55 , 56 ]. In a paper published by S. Yoshino et al in 2005, mice treated with BPA prenatally were reported to have a Th1-cytokine secretion pattern [ 57 ].…”
Section: Bisphenol a Effects On Human Healthmentioning
confidence: 99%
“…Several studies stated that BPA can bind T cells affecting Th17, Th1, and Th2 differentiation [ 50 ]. BPA significantly increased the IFN-γ and IL-4 secretion in animal models, suggesting a possible upregulation of the Th1 response [ 55 , 56 ]. In a paper published by S. Yoshino et al in 2005, mice treated with BPA prenatally were reported to have a Th1-cytokine secretion pattern [ 57 ].…”
Section: Bisphenol a Effects On Human Healthmentioning
confidence: 99%
“…Such positive antagonistic effects between parasitism and contaminant exposure could reflect sequestering of contaminants by the parasite. Stimulatory and suppressive effects of contaminants on immune parameters in endotherms have been reported (Desforges et al, 2016; Vallverdú‐Coll et al, 2019), with diverse mechanisms implicated, including interference with the aryl hydrocarbon receptor (Bou Zerdan et al, 2021; Suzuki et al, 2020). For instance, in polar bears, PCBs and OCPs have immunosuppressive effects on circulating immunoglobulin class G, production of viral antibodies, and proliferation of T and B lymphocytes (Routti et al, 2019).…”
Section: Interactive Effects Across Bioenergetic Domainsmentioning
confidence: 99%
“…Evidence has shown that AFB1-mediated oxidative stress is equally or even more responsible for AF-induced genotoxicity. The second-most documented toxicological effect of AFs is probably immunotoxicity, and its mechanisms of action (immunosuppressive and immunostimulatory actions) have been extensively illustrated [ 121 ]. Apart from the above, malnutrition, disease, impaired child growth, retardation of physical and mental maturity, reproduction, nervous system diseases, etc., are some other AF-induced acute and chronic health issues reported in mammals.…”
Section: Health Effects and Mechanism Of Toxicitymentioning
confidence: 99%